Euclidean Distance Degree of Projective Varieties. (15th November 2019) - Maxim, Laurentiu G; Rodriguez, Jose Israel; Wang, Botong
Abstract: We give a positive answer to a conjecture of Aluffi–Harris on the computation of the Euclidean distance degree of a possibly singular projective variety in terms of the local Euler obstruction function.